Low-cost energy management circuit base on primary feedback self-oscillating flyback converter for piezoelectric energy harvesting - Khemmanee, B.; Isarakorn, D. (My University, 2016)
Over the past few years, using piezoelectric elements to harvest energy from ambient vibrations has been of great interest. However, there are significant challenges in converting the power generated from the piezoelectric elements to usable form. This paper discusses the design and fabrication of off-line power supply based on a self-oscillating flyback converter. An energy management circuit was upgraded for employing in the low power generators as piezo buzzer. Since the cost per unit of the existent energy management circuit is more expensive. Therefore, this research is also to concentrate on the design of a low-cost energy management circuit that the cost is lowers than 1 USD. The primary feedback self-oscillating flyback converter was considered due to its simplicity and low component count. In addition, this circuit also operates as buck-boost converter which is more appropriate for integrating to low power generator with unsteady and low output voltage. For the experimental setup, the circuit was defined to work with 2.5-5 V input voltage. It is able to achieve the good output voltage regulation 5 V +/-6% at the 10 mA maximum current consumption of load.
Keywords: Energy harvesting; Energy management circuit; Piezoelectric impact type generator